2021
DOI: 10.1093/ecco-jcc/jjab033
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of a Self-Assembling Peptide Hydrogel to Treat Colonic Injuries Associated with Inflammatory Bowel Disease

Abstract: Background and Aims The Self-assembling Peptide Hydrogel (SAPH, PuraMatrix TM), a fully synthetic peptide solution designed to replace collagen, has recently been used to promote mucosal regeneration in iatrogenic ulcers following endoscopic submucosal dissection. Herein, we evaluated its utility in ulcer repair using a rat model of topical trinitrobenzene sulfonic acid (TNBS)-induced colonic injuries. Methods Colonic injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…We chose continuous observation for one week after TNBS induction as the time window for evaluation as studies have shown that injury can completely disappear on day 7 after TNBS, making it difficult to compare efficacy among groups [ 58 ]. As such, an observation time of seven days was considered to be optimal.…”
Section: Resultsmentioning
confidence: 99%
“…We chose continuous observation for one week after TNBS induction as the time window for evaluation as studies have shown that injury can completely disappear on day 7 after TNBS, making it difficult to compare efficacy among groups [ 58 ]. As such, an observation time of seven days was considered to be optimal.…”
Section: Resultsmentioning
confidence: 99%
“…Purposefully created periodontal defects in rats showed significant healing and bone regeneration at 4 weeks when defects were initially filled with 2.5% RADA16 solution compared to defects filled with Matrigel (a mouse-derived ECM-like product) or left unfilled ( Takeuchi et al, 2016 ). In a rat model of inflammatory colitis simulated by chemically induced colon mucosal ulceration, topical application of 1% RADA16 (as PuraMatrix) significantly suppressed colonic injury as viewed by endoscopy, downregulated expression of inflammatory cytokines, and increased expression of wound-healing factors ( Araki et al, 2021 ). Topical application of RADA16 in an assessor-blinded porcine EMR study suggested enhanced neomucosal coverage and less submucosal damage with RADA16 versus no-RADA16 treatment, at 6 days after lesion creation ( Tsiamoulos et al, 2017 ).…”
Section: Rada16 For Wound Healing and Tissue Regenerationmentioning
confidence: 99%
“…Brain mouse sections Monitor spatial distribution of lipids (cholesterol, sulfatides, phosphatidylinositols, and phosphatidylcholines). with a cluster ion beam Bi 3 + 10 keV, was used first to detect SAPH in rat models suffering from colonic injuries, and second to prove that SAPH is a propitious therapeutic approach for inflammatory bowel diseases, especially colonic ulcers (Araki et al, 2021). Earlier in the same year, Wenli et al investigated the spatiotemporal localization of lipid metabolites to identify potential biomarkers and to understand atherosclerosis (AS) pathology.…”
Section: Cliff Et Al (2003)mentioning
confidence: 99%